Cutting capacity and strength of single grinding grains; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Lyukshin V. S. Vladimir Sergeevich (Innovative technologies for producing and machining materials in mechanical engineering, 2015)
Title screen